Risk factors for falls and fall-related injuries among community-dwelling older adults in Korea: A longitudinal study - Beomman Ha; Seonho Kim (Journal of Korean Gerontological Nursing, 2026)
Purpose: This study aimed to identify risk factors for falls and fall-related injuries among community-dwelling older adults in Korea. Methods: This longitudinal study analyzed 3,186 adults aged 65 or older using nationally representative data from the Korean Longitudinal Study of Aging across three waves (2018, 2020, and 2022). We conducted multiple logistic regression analyses to identify risk factors for falls and fall-related injuries. Results: Over the 4-year follow-up, 148 participants (4.6%) experienced a fall, and 118 of these (79.7% of fallers) sustained a fall-related injury. The risk of falls increased with advanced age (odds ratio [OR]=2.01, 95% confidence interval [CI]=1.37~2.96), female sex (OR=1.64, 95% CI=1.07~2.52), lower self-rated health (OR=1.94, 95% CI=1.01~3.77), and being underweight (OR=2.71, 95% CI=1.36~5.42) or obese (OR=1.69, 95% CI=1.11~2.55). For fall-related injuries, significant risk factors included advanced age (OR=1.74, 95% CI=1.14~2.65), female sex (OR=1.71, 95% CI=1.06~2.75), lower self-rated health (OR=2.61, 95% CI=1.22~5.59), and being underweight (OR=3.01, 95% CI=1.46~6.20). Conclusion: These findings indicate that falls and fall-related injuries among older adults are complex health issues that extend beyond simple physical problems. Further research should continue to identify risk factors through repeated studies and support the development and implementation of comprehensive education and intervention programs that address the risk factors identified in this study.